2015
DOI: 10.4103/0970-2113.164148
|View full text |Cite
|
Sign up to set email alerts
|

Transbronchial lung biopsy in patients with diffuse parenchymal lung disease without 'idiopathic pulmonary fibrosis pattern' on HRCT scan - Experience from a tertiary care center of North India

Abstract: Background:Diffuse parenchymal lung diseases (DPLD) are a group of disorders characterized by chest radiological findings of bilateral diffuse shadowing. Lung biopsy is generally required to make an etiological diagnosis of DPLD's. Transbronchial lung biopsy (TBLB) is a minimally invasive method to achieve a lung sample which has been found to be a useful diagnostic tool in patients with DPLD. As per American Thoracic Society guidelines for management of idiopathic interstitial pneumonias, TBLB is not required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 5 publications
1
9
0
1
Order By: Relevance
“…Among all spontaneously breathing patients undergoing bronchoscopy with TBB, the reported risk of pneumothorax ranges from 1–6% (Table 2) [3,10–33]. In a study by Sindhwani and others transbronchial biopsies were performed only in patients with diffuse parenchymal lung disease (without a definite UIP pattern) on CT scan [37]. This study reported a 10% incidence of iatrogenic PTX following TBB, which is higher than previously reported rates for all spontaneously breathing subjects undergoing the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Among all spontaneously breathing patients undergoing bronchoscopy with TBB, the reported risk of pneumothorax ranges from 1–6% (Table 2) [3,10–33]. In a study by Sindhwani and others transbronchial biopsies were performed only in patients with diffuse parenchymal lung disease (without a definite UIP pattern) on CT scan [37]. This study reported a 10% incidence of iatrogenic PTX following TBB, which is higher than previously reported rates for all spontaneously breathing subjects undergoing the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic yield of a TBLB specimen is high in ILD with a peribronchovascular or centrilobular pattern of distribution such as sarcoidosis, HP, PAP, lymphangitis carcinomatosis, and alveolar microlithiasis. [ 19 ] Recent reports suggest the utility of TBLB for molecular diagnosis of UIP. [ 20 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Bleeding (1%–4%), pneumothorax (1%–6%), and mortality (<0.05%) constitute the main complications. [ 16 19 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the original article titled, “Transbronchial lung biopsy (TBLB) in patients with diffuse parenchymal lung disease (DPLD) without ‘idiopathic pulmonary fibrosis (IPF) pattern’ on high resolution computed tomography scan–Experience from a tertiary care centre of North India” by Sindhwani et al . [ 1 ] First, we would like to congratulate the authors for their excellent diagnostic yield of TBLB (85.6%). According to the earlier published literature, in DPLD, histological support for a specific diagnosis can be obtained using TBLB in 29–79% of cases only.…”
mentioning
confidence: 99%